Social Media Engagement in Ethical Consumption: the Role of Social Media Content and Customer Attitudes for engaging with Commercial Organisation’s Social Media Sites - ZHENG, YULAN (2017)
Customer engagement has become the focus of developing relationship between buyers and sellers, which can be seen as a concept that is critical to the success of organizations. The social media presence of organizations initiated a more interactive and communicative way of customer engagement. In the ethical consumption context, social media content has been considered to be effective in influencing consumers’ decision making process. The paper extends existing research of consumer engagement, describing in more detailed differences in individuals’ feelings, beliefs and attitudes related to an organization’s social media content. In particular, this research focus on the consumer engagement with a FT coffee brand’s social media page. A qualitative research was conducted to gain the in-depth understanding of consumer’s attitude towards information, community and action content on social media. The results supported previous literature about social media engagement, but were biased due to personal considerations in terms of the commercial organization as well as the FT products.